Understanding the injuries and environments of vulnerable healthcare workers in Liberia and Ghana: a qualitative study - Ridge, Laura Jean; McCullagh, Marjorie; Ananzeh, Tharaa; Zeantoe, G. Clinton; Aziato, Lydia; Arko-Mensah, John (International Journal of Infection Control, 2026)
Background: While sharps injuries are a hazard to healthcare workers globally, research has concentrated on high-income regions. West Africa, including Liberia and Ghana, has high rates of human immunodeficiency virus and hepatitis B virus infections, which can be transmitted via sharps injury. Use of safety-engineered devices is highly limited in this region. Objective: To explore factors contributing to frequent sharps injuries and underreporting among health care workers in Liberia and Ghana, and to recommend potential interventions. Design: Semi-structured interviews were conducted via an Internet-enabled platform among nurses, midwives, physicians and physician assistants in Liberia and Ghana. Questions focused on injury history, sharps injury prevention, and work environment. Interview transcripts were analyzed deductively. Recruitment ended when data saturation was reached. Results: Sixteen interviews were conducted among seven Liberian and nine Ghanaian healthcare workers. Unexpected patient movement and colleagues contributed to seven of 16 injuries. Prelicensure sharps injury prevention training was limited, though more accessible post licensure. Many participants desired more training. Most (n = 12) did not report their injuries. While many viewed their work environment as adequate, others noted specific issues, including inadequate sharps disposal containers and limited supplies. Discussion: Training deficiencies and systemic gaps were key contributors to injury and underreporting. Respondents showed interest in enhanced training and clearer procedures. Conclusion: The results of this study suggest ways to reduce sharps injuries in Ghana and Liberia, including additional training for workers and more accessible sharps disposal containers. Materials developed to train these workers have the potential to be useful to workers anywhere resources are constrained.